1991
DOI: 10.1063/1.106113
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum field emission from a Si-TaSi2 semiconductor-metal eutectic composite

Abstract: We report on measurements of vacuum field emission from ungated field emission cathode arrays fabricated from Si-TaSi2 eutectic composite wafers. The Si-TaSi2 material is an ideal candidate for large area field emission array cathodes due to the large density of TaSi2 fibers incorporated into the Si matrix, the high melting point of the TaSi2 material, the ease with which single-crystal large diameter (2.5 cm) material can be fabricated, and the promise of integrability of the field emission array with convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…As one of the semiconductor-metal eutectic (SME) composites, the Si-TaSi 2 eutectic in situ composite has obtained more and more attention recently. In 1980s Ditchek et al [1,2] have successfully prepared Si-TaSi 2 eutectic in situ composite by Czochralski (CZ) crystal growth technique, and then Kirkpatrick et al [3] have reported the vacuum field emission of the Si-TaSi 2 SME composite and patented its application in 1999 [4]. However, the TaSi 2 fibers are not uniformly distributed and the inter-rod spacing of the TaSi 2 fibers is relatively large, because of the restriction of lower growth rate of CZ method [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the semiconductor-metal eutectic (SME) composites, the Si-TaSi 2 eutectic in situ composite has obtained more and more attention recently. In 1980s Ditchek et al [1,2] have successfully prepared Si-TaSi 2 eutectic in situ composite by Czochralski (CZ) crystal growth technique, and then Kirkpatrick et al [3] have reported the vacuum field emission of the Si-TaSi 2 SME composite and patented its application in 1999 [4]. However, the TaSi 2 fibers are not uniformly distributed and the inter-rod spacing of the TaSi 2 fibers is relatively large, because of the restriction of lower growth rate of CZ method [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation and application of the Si-TaSi 2 eutectic in situ composite by the Czochralski (CZ) crystal growth technique have been reported [1][2][3][4]. However, TaSi 2 fibers are not uniformly distributed and the inter-rod spacing of the TaSi 2 fibers is relatively large, because of the restriction of the lower growth rate of the CZ method [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Ditchek et al [9,10] studied the Czochralski-grown semiconductor-based eutectic for electronic applications in late 1980s. Then Kirkpatrick et al [11,12] reported the field emission property and applications of this material.…”
Section: Introductionmentioning
confidence: 99%